2015
DOI: 10.1007/s00383-015-3773-1
|View full text |Cite
|
Sign up to set email alerts
|

Severe acquired subglottic stenosis in children: analysis of clinical features and surgical outcomes based on the range of stenosis

Abstract: The range of stenosis was affected by the period and duration of endotracheal intubation. Surgical outcomes of LTR tended to differ between localized SGS and extended SGS. LTR can be effective for localized SGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
4
3
0
Order By: Relevance
“…3 Similarly, no significant difference was reported in regard to gender by Morita et al in 33 pediatric patients (16 male/17 female). 9 In our study, gender had no effect on the development of SGS, in accordance with literature. Many studies on post-intubation SGS have been conducted primarily on premature babies because of their long intubation periods 5,10 ; however, the state of maturity had no effect on the development of SGS as shown in our patients.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…3 Similarly, no significant difference was reported in regard to gender by Morita et al in 33 pediatric patients (16 male/17 female). 9 In our study, gender had no effect on the development of SGS, in accordance with literature. Many studies on post-intubation SGS have been conducted primarily on premature babies because of their long intubation periods 5,10 ; however, the state of maturity had no effect on the development of SGS as shown in our patients.…”
Section: Discussionsupporting
confidence: 92%
“…3 Similarly, the study by Morita et al, conducted on 33 pediatric patients, reported that 29 patients had grade 3 SGS. 9 In our study, 50% of our patients showed grade 3 stenosis, which is similar to the literature.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations